The system of urban public spaces in the post-communist sociocultural context - Grunskis, Tomas; Mankus, Martynas (Journal of Architecture and Urbanism, 2013)
The article analyses the system of urban public spaces and discusses its current situation in the changed sociocultural context of Lithuania. The concept of the system of urban public spaces is approached as a relevant problem, by focusing on the ideological aspects of public space formation. Also, the problem of current transformation of main public spaces in Lithuanian largest towns is discussed considering the background of still persistent post-communist sociocultural situation. In the context of such sociocultural environment, a case of public space development in Šiauliai is presented as one of the most interesting and significant, related to the ideological changes in Lithuania before 1990. Key models of urban public space formation are reviewed in the article with assumptions being made on their possible influence on the situation in Lithuania. Miesto viešųjų erdvių sistema postkomunistinėje sociokultūrinėje aplinkoje Santrauka. Straipsnyje nagrinėjamas miesto viešųjų erdvių sistemos klausimas ir aptariama esamą jų padėtis pakitusioje sociokultūrinėje aplinkoje Lietuvoje. Jame aktualizuojama miesto viešųjų erdvių sistemos koncepcijos problema, nagrinėjami ideologiniai viešųjų erdvių formavimo aspektai. Aktualizuojama dabartinė didžiųjų Lietuvos miestų pagrindinių viešųjų erdvių kaitos problema užsitęsusioje postkomunistinėje sociokultūrinėje situacijoje. Sociokultūrnės aplinkos kontekste kaip vienas įdomesnių ir svarbesnių aptariamas Šiaulių miesto viešųjų erdvių plėtros atvejis, kuris susiejamas su ideologine kaita Lietuvoje iki 1990 m. Straipsnyje apžvelgiami pagrindiniai miestų viešųjų erdvių formavimo modeliai ir daromos prielaidos dėl jų galimos įtakos Lietuvos situacijai. Reikšminiai žodžiai: miesto viešųjų erdvių sistema, postkomunistinis.